Physical and functional interaction between integrins and hERG potassium channels. (26th October 2004) - Arcangeli, A.; Becchetti, A.; Cherubini, A.; Crociani, O.; Defilippi, P.; Guasti, L.; Hofmann, G.; Pillozzi, S.; Olivotto, M.; Wanke, E.
Abstract : Integrins are adhesion receptors capable of transmitting intracellular signals that regulate many different cellular functions. Among integrin-mediated signals, the activation of ion channels can be included. We demonstrated that a long-lasting activation of hERG (h uman e ther-a-go-go-r elated g ene) potassium channels occurs in both human neuroblastoma and leukaemia cells after the activation of the β1 integrin subunit. This activation is apparently a determining factor inducing neurite extension and osteoclastic differentiation in both the cell types. More recently, we provided evidences that β1 integrins and hERG channels co-precipitate in both the cell types. Preliminary results suggest that a macromolecular signalling complex indeed occurs between integrins and the hERG1 protein and that hERG channel activity can modulate integrin downstream signalling.